Low-grade oncocytic tumour expands the spectrum of renal oncocytic tumours and deserves separate classification: a review of 23 cases from a single tertiary institute. Issue 11 (24th June 2021) - Akgul, Mahmut; Al-Obaidy, Khaleel I; Cheng, Liang; Idrees, Muhammad T
Abstract : Aims: Low-grade oncocytic tumour (LOT) has recently been introduced as a potential distinct entity. Methods: At the Indiana University department of pathology, primary renal epithelial neoplasms between 2005 and 2020 were searched after appropriate institutional review board permissions. Results: Twenty-three cases (male/female ratio 14/9) with a median age of 66 (23–84 years) were identified. The majority of patients underwent partial nephrectomy (15/23, 65%), with a median tumour size of 4.0 cm (2.2–10.5 cm). Only one case had infiltration beyond the kidney (perinephric fat). Solid/diffuse proliferation of tightly packed oncocytic tumour cells and occasional tubule formations, with an abrupt edematous change in the stroma with loosely connected small clusters of tumour cells. Along with diffuse CK7 expression with lack of CD117 in all cases, vimentin was positive in 8/23 cases (35%, 5 focal). CD10 was expressed in 6/13 (46%, 4 focal). Alpha-Methylacyl-CoA Racemase (AMACR) was positive in 5/8 (63%) cases. Focal but intense cytoplasmic colloidal iron stain was present in 3/20 (15%) cases. Luminal or cytoplasmic/perinuclear precipitation was observed in 8/20 (40%) cases. Succinate Dehydrogenase B (SDHB) was performed in 6 cases, with all retained expression. Conclusions: LOT is a clinically indolent and potentially benign entity with distinguishable morphology and immunohistochemical profile that can be performed and be easily interpreted in most of surgical pathology settings. Additional studies with larger cohorts, comprehensive molecular evaluation and longer follow-up are needed to definitively recognise these tumours as a separate entity and to further address the possibility of active surveillance options in eligible patients.